1981
DOI: 10.2519/jospt.1981.2.3.134
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study: Application of Ultrasound to Determine a Stress Fracture of the Fibula

Abstract: A 35-year-old female was referred to physical therapy for evaluation and treatment of a left ankle condition diagnosed as an acute sprain. The diagnosis was based in part on a patient history of mild ankle sprains. In this incidence, as in the past, the patient's family physician attributed the ankle problem to her body weight of 318 pounds in combination with the duties required of her as a janitor.The patient was questioned regarding the problem with the left ankle. The patient was most emphatic in her denia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Therapeutic US Ultrasound transducers for therapeutic US are characterized by a low US frequency for treating clinical conditions in the physical therapy clinic and not for the visualization of structures. 23,[44][45][46] . The first of several articles using therapeutic US for the diagnosis of early bone stress injuries were published in the 1980s.…”
Section: Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic US Ultrasound transducers for therapeutic US are characterized by a low US frequency for treating clinical conditions in the physical therapy clinic and not for the visualization of structures. 23,[44][45][46] . The first of several articles using therapeutic US for the diagnosis of early bone stress injuries were published in the 1980s.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Ultrasound transducers for therapeutic US are characterized by a low US frequency for treating clinical conditions in the physical therapy clinic and not for the visualization of structures …”
Section: Historical Review Of Imaging Modalities Used In the Diagnosimentioning
confidence: 99%
“…Some authors have suggested that ultrasound may be useful in the early identification of stress fractures (Delacerda 1981;Moss and Mowat 1983). Continuous ultrasound at 0.75 MHz with an intensity of 1 .O -2.0 Wcmover the site of fracture i s reported to cause pain (Moss and Mowat 1983) but the sensitivity and specificity of this test has not been verified.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Even though MRI is the standard for diagnosis, therapeutic ultrasound (TUS) was used back in the early 1980s to detect bone stress injuries earlier than plain radiography. 3,6,17 Therapeutic ultrasound is increasingly being used in the evaluation of the musculoskeletal system and has recently been shown to have some potential in the diagnosis of stress injuries. 16 Although designed primarily as a therapeutic modality, TUS is not only used in the treatment of soft tissue sport injuries, but it is also an accurate, cost-efficient diagnostic alternative to imaging methods for the primary assessment of bone stress injuries because direct application of TUS at the site of injury may produce pain, thus confirming the diagnosis.…”
mentioning
confidence: 99%
“…16 Although designed primarily as a therapeutic modality, TUS is not only used in the treatment of soft tissue sport injuries, but it is also an accurate, cost-efficient diagnostic alternative to imaging methods for the primary assessment of bone stress injuries because direct application of TUS at the site of injury may produce pain, thus confirming the diagnosis. 3,4,6,7,17 Therapeutic ultrasound, being cost-effective, safe, and noninvasive, may be used as a preliminary assessment tool in this context. Our aim was to detect whether TUS is a reliable method for the early diagnosis of bone stress injuries compared with the gold standard method, namely MRI.…”
mentioning
confidence: 99%